(untitled) (Homiletic, 2024)
This article considers the connection between preaching and power in search of a more inclusive understanding of preaching and more expansive modes of sermonic expression. As feminist and postcolonial theologians repeatedly emphasize, the pulpit, in both a concrete and symbolic sense, remains oriented toward white male preachers. German-language education also continues to be dominated by this perspective. Drawing on interdisciplinary theories of power and postcolonial theology, the concluding section of this paper introduces five dimensions of homiletical practice aimed at making preaching more sensitive to power dynamics: sharing interpretive power, starting from religious experience and lived theology; taking the body seriously (embodiment); daring polyphony; and imagining and acting together on the kingdom of God.